Re-examination of the anion derivatives of isoflavones by radical fragmentation in negative electrospray ionization tandem mass spectrometry: experimental and computational studies - Vessecchi, Ricardo; Zocolo, Guilherme Juliao [UNESP]; Gouvea, Dayana Rubio; Huebner, Florian; Cramer, Benedikt; Rodrigues de Marchi, Mary Rosa [UNESP]; Humpf, Hans-Ulrich; Lopes, Norberto P. (Wiley-Blackwell, 2011)
This paper reports theoretical and experimental studies of gas-phase fragmentation reactions of four naturally occurring isoflavones. The samples were analyzed in negative ion mode by direct infusion in ESI-QqQ, ESI-QqTOF and ESI-Orbitrap systems. The MS/MS and MS(n) spectra are in agreement with the fragmentation proposals and high-resolution analyses have confirmed the formulae for each ion observed. As expected, compounds with methoxyl aromatic substitution have showed a radical elimination of center dot CH(3) as the main fragmentation pathway. A second radical loss (center dot H) occurs as previously observed for compounds which exhibit a previous homolytic center dot CH(3) cleavage (radical anion) and involves radical resonance to stabilize the anion formed. However, in this study we suggest another mechanism for the formation of the main ions, on the basis of the enthalpies for each species. Compounds without methoxy substituent dissociate at the highest energies and exhibit the deprotonated molecule as the most intense ion. Finally, energy-resolved experiments were carried out to give more details about the gas-phase dissociation reaction of the isoflavones and the results are in agreement with the theoretical approaches. Copyright (C) 2011 John Wiley & Sons, Ltd.